THE DYNAMICS OF TEACHING FINANCIAL EDUCATION IN ELEMENTARY SCHOOL (CIPEEX, 2025)
The introduction of financial education from childhood is essential to form conscious and responsible citizens in the use of money. This project, initiated in 2023 and expanded in 2024, aims to promote financial understanding in children, addressing topics such as budgeting, saving, and conscious consumption. Conducted with elementary school students in Rubiataba, the event used interactive methods, including presentations and a "pie in the face" game, to consolidate learning in a playful and effective way. The results indicate increased understanding of personal finances, with positive feedback from students and teachers, reinforcing the importance of continuous educational practices for a responsible financial future.
Keywords: Children's financial education; Conscious consumption; Financial responsibility; Educational project; Playful interaction